Evacuation safety for elderly residents in public multi-storey residential building in Malaysia / Nurul Liyana Hanapi - Hanapi, Nurul Liyana (2019)
The main concern of this study is on the increase in the elderly population living in multi-storey residential buildings. The second concern is on these elderlies’ safety aspects including slow speed, physical mobility and fall prevention. Only a few studies were found to have assessed the needs and safety measures of elderlies during emergency situations. Coupled with the rapid development of high-rise buildings, the safety of elderlies has fast become a major concern as they fall under the vulnerable group of people due to their slower walking speed and limitations to their physical mobility capability. Thus, the first objective of the study is to identify the reactions and perceptions of elderly occupants towards evacuation safety procedures in PPR buildings. It was found that elderlies behave similarly with adults, but concerns over personal belongings could cause hesitations during the evacuation process. Then, the second objective is to evaluate experts’ opinions on the safety measures implemented in public multi-storey residential buildings in Malaysia. The survey results revealed that the passive design scored the highest mean in terms of evacuation efficiency. The next step of this research was conducting analysis using the Pathfinder software to answer the next objective, which is to analyse the variants in escape route design and the effect of evacuation efficiency on both elderly and adult occupants. As public multi-storey residential buildings only follow the minimum requirements set according to the UBBL 1984, these buildings are viewed as a suitable subject to be studied. Before the simulation process was conducted, the study conducted a case study on three public multi-storey residential buildings. All three building layouts showed similar issues that contribute to longer evacuation time. Then, a simulation was conducted with three main focuses in order to understand the effect of staircases’ physical condition towards the evacuation process, the effect of the elderly’s dwelling position on their speed of movement, and the effect of varying distances and widths of escape route elements (corridor, staircase and exit) on the evacuation time. The results firstly showed a high dependency on staircases as they have a significant contribution towards evacuation time, and that crowd dispersal patterns contribute to issues of stagnation at staircases. The results also showed that elderly occupants who occupy units on the lower levels experience faster and shorter evacuation times without affecting other evacuees. Lastly, the results show that increasing the staircases’ width to 1500mm can significantly decrease the total evacuation time. The findings helped the study develop an evacuation safety model to suit the increasing number of elderly occupants in public multi-storey residential buildings which is the fourth objective of the study. The model is subdivided into four categories which are fire safety awareness, equipment and evacuation skills, maintenance and management, and fire safety design. The outcomes of the study contribute to the understanding of the elderlies' behaviour during emergency situations and safety implementation in terms of building design based on experts’ view, highlight the common issues arising in public multi-storey housing, and contribute to the knowledge on crowd dispersal in public multi-storey residential buildings